Role of Bile Acids in Bariatric Surgery - Wang, Wenting; Cheng, Zhiqiang; Wang, Yanlei; Dai, Yong; Zhang, Xiang; Hu, Sanyuan (Frontiers in Physiology, 2019)
Bariatric surgery has been proved to be effective and sustainable in the long-term weight-loss and remission of metabolic disorders. However, the underlying mechanisms are still far from fully elucidated. After bariatric surgery, the gastrointestinal tract is manipulated, either anatomically or functionally, leading to changed bile acid metabolism. Accumulating evidence has shown that bile acids play a role in metabolic regulation as signaling molecules other than digestive juice. And most of the metabolism-beneficial effects are mediated through nuclear receptor FXR and membrane receptor TGR5, as well as reciprocal influence on gut microbiota. Bile diversion procedure is also performed on animals to recapitulate the benefits of bariatric surgery. It appears that bile acid alteration is an important component of bariatric surgery, and represents a promising target for the management of metabolic disorders.